Students' Perception of Using Quizizz Gamification for English learning in Islamic Education - Hasanah, Nur (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Gamification, or the use of game qualities outside of a game setting to influence learning-related behaviors or attitudes, is seen as a novel approach to meeting the various requirements of students with learning or behavioral issues. Quizizz, a game-based online exam that enables engaging multiplayer teaching activities and allows learners to practice with their devices, is one of the most popular digital educational games. The purpose of this study was to find out how Quizizz, a formative assessment tool, was perceived by students at the "State Islamic Institute" Ponorogo (IAIN Ponorogo) in English class. The participants of this study were first-year Islamic education students studying English who were given a formative test using Quizizz for a half of first semester. This study employed a descriptive qualitative research approach, gathering data via questionnaires to understand the ways in which Quizizz impacted the areas of motivation, engagement, satisfaction, and enjoyment. All of the questionnaire's questions had a strongly positive response, according to the results, which were supported by the secondary data from the interview, demonstrating how positively students felt about Quizizz in the classroom. The excellent reception of Quizizz in English language learning suggests that it could be utilized more broadly as a formative evaluation tool in language acquisition. The findings indicate that gamification can be an effective strategy to engage and motivate students to learn. As a result, educators may wish to consider incorporating further gamified tools and strategies into the classroom to create a more pleasurable and engaging learning environment.